2015
DOI: 10.1097/mao.0000000000000900
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effectiveness for Symptoms of Patulous Eustachian Tube

Abstract: The available evidence for management of patients with PET is poor in quality and consists predominantly of small case series. Further research is needed to determine the comparative efficacy of the current treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Half of patients experienced resolution of their PETD symptoms lasting over 1 year, similar to rates of symptom resolution reported in two recent meta‐analysis . There were differences, however, among the procedures in the duration of symptom resolution.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Half of patients experienced resolution of their PETD symptoms lasting over 1 year, similar to rates of symptom resolution reported in two recent meta‐analysis . There were differences, however, among the procedures in the duration of symptom resolution.…”
Section: Discussionsupporting
confidence: 80%
“…Half of patients experienced resolution of their PETD symptoms lasting over 1 year, similar to rates of symptom resolution reported in two recent meta-analysis. 25,26 There were differences, however, among the procedures in the duration of symptom resolution. Placement of a shim had lower rates of failure at 12 months compared to injection of calcium hydroxyapatite cement and to procedures intending to reconstruct the ET lumen.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To our knowledge, this is the first prospective and multicenter case series of surgical treatment for PET. Two systematic reviews regarding surgical procedures for PET had been reported in 2015 . Several surgical methods have been reported, including manipulation of TM, injection into the submucosa of the ET, shim surgery, plug surgery, ET reconstruction, and permanent closure of the ET.…”
Section: Discussionmentioning
confidence: 99%
“…computed tomography or tympanometry) have been used to improve the diagnosis of patulous Eustachian tube, it remains a clinical diagnosis based on mentioned symptoms and visualisation of tympanic membrane movement with respiration. 4 There is currently no general consensus regarding patulous Eustachian tube management. A variety of non-surgical treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%